2001
DOI: 10.1136/ard.60.10.946
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E is ineffective for symptomatic relief of knee osteoarthritis: a six month double blind, randomised, placebo controlled study

Abstract: Objective-There is a putative role for antioxidant treatment in osteoarthritis (OA) based on animal, epidemiological, and human clinical studies. Vitamin E, a fat soluble vitamin, is one of the major dietary antioxidants. Short term clinical studies using vitamin E in the form of -tocopherol suggested a benefit over placebo of similar dimension to that of diclofenac for relief of OA pain. Methods-A six month, double blind, randomised, placebo controlled study of vitamin E 500 IU/day was carried out. Primary ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(31 citation statements)
references
References 18 publications
0
30
0
1
Order By: Relevance
“…6 However, there is also a controversial report on the inefficacy of vitamin E in the management of arthritis. 54 Furthermore, despite the massive efforts of researchers and various therapeutic triumphs, we know little about the genesis of arthritis with senescence, or its prevention, and there is a need for further research and the discovery of novel markers for early intervention in the geriatric population.…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…6 However, there is also a controversial report on the inefficacy of vitamin E in the management of arthritis. 54 Furthermore, despite the massive efforts of researchers and various therapeutic triumphs, we know little about the genesis of arthritis with senescence, or its prevention, and there is a need for further research and the discovery of novel markers for early intervention in the geriatric population.…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…For example, it has been reported that human plasma g-tocopherol is positively associated with osteoarthritis, whereas plasma a-tocopherol is negatively associated with osteoarthritis (66). In contrast, in another report on knee osteoarthritis, vitamin E supplementation (a-tocopherol) did not relieve symptoms, but the authors did not measure patient a-tocopherol or g-tocopherol levels (67). In coronary heart disease and stroke, studies of tocopherols and heart disease are complex, because different dietary oils not only contain different forms of tocopherols but also contain different lipids that affect heart disease.…”
mentioning
confidence: 97%
“…Considerable attention has been devoted to the potential use of α-tocopherol, a potent chain breaking antioxidant, in the prevention of age-related complications [Yu et al 1998]. Although in previous clinical studies vitamin E has been found to be effective in the symptomatic treatment of arthritis and osteoporosis [Edmonds et al 1997;Chavan et al 2007], controversial reports on the inefficacy of vitamin E in the management of OA have been documented [Brand et al 2001]. The mechanism underlying its effect in ameliorating the enzyme activities, levels of MDA (i.e.…”
Section: Protection Of Chondrocytes From Potentially Injurious Superomentioning
confidence: 99%